In-utero and childhood chemical exposome in six European mother-child cohorts. (December 2018) - Haug, Line Småstuen; Sakhi, Amrit Kaur; Cequier, Enrique; Casas, Maribel; Maitre, Léa; Basagana, Xavier; Andrusaityte, Sandra; Chalkiadaki, Georgia; Chatzi, Leda; Coen, Muireann; de Bont, Jeroen; Dedele, Audrius; et al.
Abstract: Background: Harmonized data describing simultaneous exposure to a large number of environmental contaminants in-utero and during childhood is currently very limited. Objectives: To characterize concentrations of a large number of environmental contaminants in pregnant women from Europe and their children, based on chemical analysis of biological samples from mother-child pairs. Methods: We relied on the Early-Life Exposome project, HELIX, a collaborative project across six established population-based birth cohort studies in Europe. In 1301 subjects, biomarkers of exposure to 45 contaminants (i.e. organochlorine compounds, polybrominated diphenyl ethers, per - and polyfluoroalkyl substances, toxic and essential elements, phthalate metabolites, environmental phenols, organophosphate pesticide metabolites and cotinine) were measured in biological samples from children (6–12 years) and their mothers during pregnancy, using highly sensitive biomonitoring methods. Results: Most of the exposure biomarkers had high detection frequencies in mothers (35 out of 45 biomarkers with >90% detected) and children (33 out of 45 biomarkers with >90% detected). Concentrations were significantly different between cohorts for all compounds, and were generally higher in maternal compared to children samples. For most of the persistent compounds the correlations between maternal and child concentrations were moderate to high (Spearman Rho > 0.35), while for most non-persistent compounds correlations were considerably lower (Spearman Rho < 0.15). For mercury, PFOS and PFOA a considerable proportion of the samples of both mothers and their children exceeded the HBM I value established by The Human Biomonitoring Commission of the German Federal Environment Agency. Discussion: Although not based on a representative sample, our study suggests that children across Europe are exposed to a wide range of environmental contaminants in fetal life and childhood including many with potential adverse effects. For values exceeding the HBM I value identification of specific sources of exposure and reducing exposure in an adequate way is recommended. Considerable variability in this "chemical exposome" was seen between cohorts, showing that place of residence is a strong determinant of one's personal exposome. This extensive dataset comprising >100, 000 concentrations of environmental contaminants in mother-child pairs forms a unique possibility for conducting epidemiological studies using an exposome approach. Highlights: Children across Europe are exposed to a wide range of environmental contaminants. Considerable variability in the "chemical exposome" was seen between cohorts. Significant differences in concentrations between mothers and children were found.